THE SPATIAL PLANNING TO IMPLEMENT SUSTAINABLE AGRICULTURAL LAND - Lego Karjoko, Soediro, I Gusti Ayu Ketut Rachmi Handayani (International Journal of Advanced Science and Technology, 2020)
Indonesia is an agricultural producing country; the agricultural sector becomes its main economic base. Empirically, most of Indonesians work in this sector as their livelihood. Article No. 33 Chapter (3) of Undang-undang Dasar 1945 (The 1945 Constitution of The Republic of Indonesia) states a role of the state in managing and regulating land. It is clearly declared that land, water and natural resources contained therein are owned by the state and used as much as possible for the prosperity of the people of Indonesia. Land conversion is usually related to the process of regional development, even it can be said that the land conversion is a consequence of the development. In fact, most of the land conversion shows an imbalance dominated by business owners who are alleged to be modern capitalists having Building Construction Permits (IMB) issued by the government. Based on Regulation of Government No. 1 of 2011 concerning Determination and Land Conversion of Sustainable Agricultural Land, it is a field of agricultural land determined to be consistently protected and developed to produce staple food for the autonomy, resilience and sovereignty of foods for the nation.